Carbon Monoxide Poisoning during Pregnancy: Presentation of a Rare Severe Case with Fetal Bladder Complications - Myriam Delomenie; Floriane Schneider; Joëlle Beaudet; René Gabriel; Nathalie Bednarek; Olivier Graesslin (Case Reports in Obstetrics and Gynecology)
Carbon monoxide poisoning during pregnancy is a rare and potentially serious condition. Fetal complications are uncommon, related to anoxic lesions. The severity of these complications does not depend on the level of maternal COHb. We report the case of a 22-year-old pregnant woman who at 30 weeks of gestation had carbon monoxide poisoning secondary to a fire in her home, complicated by cardiac arrest and severe fetal damage. The child had not brain damage, but presented bladder lesions not previously described, with urinary ascites complicating megacystis.